Effect of proteases against biofilms of Staphylococcus aureus and Staphylococcus epidermidis. (1st November 2014) - Elchinger, P.‐H.; Delattre, C.; Faure, S.; Roy, O.; Badel, S.; Bernardi, T.; Taillefumier, C.; Michaud, P.
Abstract: Biofilms play a key role in bacterial resistance against antibacterial agents—an issue that causes multiple problems in medical fields, particularly with Staphylococcus biofilms that colonize medical indwelling devices. The literature reports several anti‐biofilm strategies that have been applied in medicine. Disrupting the biofilm formation process creates new sites open to colonization by treatment‐generated planktonic bacteria, so efforts have turned to focus on strategies to prevent and control the initial Staphylococci adhesion. Here, we investigated the preventive activities of three commercial proteases (Flavourzyme, Neutrase and Alcalase) against biofilm formation by two Staphylococcus strains. Some proteolytic extracts revealed interesting results with Staphylococcus epidermidis and Staphylococcus aureus aureus biofilms. Significance and Impact of the Study: Three proteases were tested against Staphylococcus aureus and Staphylococcus epidermidis biofilms in standard conditions. The Flavourzyme containing a mix of Aspergillus orizae endo‐ and exoproteases demonstrated significant efficacy against Staph. epidermidis biofilm formation. These results could prove valuable in the effort to develop simple anti‐biofilm methods.